Analisis Eksperimental Waktu Respons dan Repeatabilitas Sensor Gas CCS811 terhadap Paparan Asap Rokok pada Ruang Uji Terkontrol - Billy Sopater Maniani; Akbar Sujiwa; Nailul Hasan (Universitas Andalas, 2026)
This study analyzes the response time and repeatability of a CCS811 gas sensor embedded in a self-developed wearable cigarette-smoke detector. Experiments were carried out in controlled test chambers of cm and cm using exposures of 1–4 cigarettes, with five repetitions for each condition, yielding 40 experiments. The blue mark was defined as the start of exposure, the yellow mark as the instant when the TVOC reading first reached or exceeded the internal alarm threshold of 65 and the vibration motor was activated, and the red mark as the peak value before the signal decreased. The analyzed parameters were alarm time, peak time, peak eCO2, peak TVOC, standard deviation, and coefficient of variation. The mean alarm time ranged from 35.43 to 91.98 s, while the mean peak time ranged from 76.50 to 139.29 s. The highest peaks were observed for four cigarettes, reaching 6051.4 ppm and 9389.0 ppb in the 20 cm chamber, and 5984.4 ppm and 9234.0 ppb in the 40 cm chamber. Two-way ANOVA indicated that chamber size and cigarette number significantly affected peak eCO2 and peak TVOC (p<0.01), but not response time (p>0.05). These results show that the CCS811 is feasible for trend detection of cigarette smoke exposure in low-cost wearable devices